#TITLE_ALTERNATIVE# - Setiawan (NIM 32297008), Kuswara
ABSTRACT: Following some references is so necessary to support the production process in a manufacture industry, such as when the raw materials have to be available, the quantity of the raw materials and the budget has to provide these materials. These three references should be well determined beforehand by the production staff and other departments involved, and ordering is issued afterwards. During raw materials ordering process, some disturbances may happen on three of cases, those are disturbance of time, quantity and cost. So these three variables time of ordering, the amount of raw materials to be ordered and the total cost will become the control ones. The relationship among these three control variables which become inputs of the ordering process and its output is difficult to formulate mathematically. Control variables can also be achieved by mathematics based software, but certain data may find an endless loop without any result. Therefore, the controller based on fuzzy logic is implemented since it does not need mathematical model. The first error due to the disturbances is the difference between the arrival time of raw material (which will further become output of the ordering process) and when it should arrive; the second one is between the amount of arriving raw material and that should arrive; the third error is between the cost spent by the industry and the budget. These errors become input to the controller, while the output is the control variable. With the existence of the controller, the above references become set points. The three set points are determined based on the discrete-time inventory model. The discrete-time inventory model is closer to reality than the continous one. The main difference lies on the amount of holding cost.